Surgical Corrections in a Patient with Face & Neck Burn Deformity - Karn, Binod; Mishra, S M (Journal of Nepalgunj Medical College, 2017)
Introduction: Face and neck burn deformity is the most common deformity after deformity of hand. Flame burn and chemical burn are the common causes for the all types of burn contractures. Burn contractures involving the anterior neck represent a surgical problem for the Plastic surgeons. Objective: To evaluate the outcome of patients who underwent reconstructive surgery for face and neck burn deformity. Materials and method: The study was conducted in the department of surgery in plastic surgery unit, NGMC between February 2013 to June 2015. During this period 36 patients underwent reconstructive surgery. Result: In 36 patients, there were 12 males and 24 females. The age of patients ranging from 11 years to 56 years. The overall results were satisfactory in 34 cases and not satisfactory in 2 cases, The clinical satisfaction degree was 94.44% in overall evaluation. The average follow up period was from 3 months to 1 year. Conclusion: Among the different types of contractures, neck contractures are also very frequently treated. Common surgical procedure is release of contracture and application of skin graft, the other techniques are applied like expanded or without expansion island flaps, free flaps. Finally the main objective of the different surgical approaches is to obtain the better functional and aesthetical result. JNGMC Vol. 13 No. 2 December 2015, Page: 42-45